RxBox development of portable medical equipment for an open source telemedicine system - Chiong, Charles Hernan DC.; Cornillez, Dan Simone M. (2009.)
Telemedecine is the application of telecommunications technology to provide health care services and facilitate health information exchange between two or more remote locations. It involves diagnosis, immediate treatment and medical records of patients. Most rural or even urban areas in the Philippines have limited or no access to quality health services. Moreover, the growing number of health care professionals leaving the country further aggravates the problem. A sound solution is the development of a local telemedical system. RxBox, a component of the PCHRD's research program entitled "National Telehealth Service", is an open source telemedicine plliance that collects biomedical signals from the patient. The aim of the project is to improve the functionality of the biomedical modules integrated in the RxBox software by implementing methods to check if the module is powered on, the serial port is connected and properly configured, the sensor is connected to the device and the sensor is connected to the patient. A standard 12-lead ECG display will be implemented. Auscultation is an important procedure in evaluating the cardiac system. Heart sounds can give vital information regarding the patient's heart condition. This project interfaced the Biopac SS30L Electronic Stethoscope with the RxBox Software through the line in of a computer. Digital filter is implemented to eliminate the noise and extract the heart sound signals. RxBox will be deployed in remote areas where the user will range from the local health care personnel, midwife and doctors. When referring a case from a remote area, the doctor being consulted needs to know the visual appearance of the patient and this is realized by sending snapshots form the RxBox. The prototype device for snapshot is a USB camera. Images produced by the camera are written as frames in a DICOM file, the medical standard for imaging. In addition to improving the GUI and adding devices, the project determined the Quality os Service (QoS) of the web services used. A script for automatic characterization to check the telehealth an email servers is embedded in the RxBox Software. This includes measuring the round trip delay for the telehealth server and sending a test message to the email server via Simple Mail Transfer Protocol (SMTP) server.
Thesis (B.S. Electronics and Communications Engineering) - University of the Philippines, Diliman.
Keywords: Medical instruments and apparatus -- Design and construction; Telemedicine; Portable medical equipment; RxBox Software; Telemedical system